EDUKASI TENTANG STUNTING PADA IBU BALITA DI WILAYAH KERJA PUSKESMAS BIROMARU - Suwendro, Novi Inriyanny; Ayu Wandira, Bertin; Hermiyanty; Hasanah (Jurusan Farmasi FMIPA Universitas Tadulako, 2023)
In 2017, 22.2% or around 150.8 million children under five in the world experienced stunting and more than half of stunted children under five in the world come from Asia (55%). The prevalence of stunting in Indonesia in 2019 was 27.7%, meaning that about one in four children under five in Indonesia is stunted. Central Sulawesi is one of the 10 provinces that have the highest prevalence of stunting in Indonesia and Sigi District is the district with the highest stunting prevalence reaching 40.7% in 2021. The prevalence is very high and is a serious problem that needs to be addressed quickly and appropriately. Many factors can cause stunting in toddlers, one of the most important factors is the mother's education and knowledge. Providing education to mothers can prevent stunting in toddlers. This service aims to increase the knowledge of mothers of toddlers in Sigi Regency regarding stunting. The method used is providing counseling and distributing pocket books on stunting for mothers of children under five at the Posyandu. Service activities were carried out at the UPGK Posyandu, Jono Oge Village, Sigi Regency. The partner of this service is the Biromaru Health Center. Broadly speaking, the implementation of service activities can be categorized as successful and going well. This can be shown by the entire target of service (100%) of mothers under five experiencing an increase in knowledge before and after receiving counseling and distributing pocket books. The highest increase in knowledge was knowledge about the definition of stunting, complementary feeding and the role of defecation in healthy latrines in preventing stunting, which was 40%. It is hoped that this activity can be provided continuously for mothers in every Posyandu so as to prevent stunting in the future. Keywords: education, stunting, mother's knowledge